New research findings on 11th-early 13th-century polychrome wood sculpture at the Royal Institute for Cultural Heritage, Brussels - Emmanuelle Mercier (Medievalista)
11th- to early 13th-century medieval polychrome sculptures can be considered as ancestral testimony of knowledge, practices, and the exchange of carving and painting techniques in the Middle Ages. This paper aims to provide an analysis of 50 years of research in Belgium, including recent case studies. New material elements and analysis results will likely resuscitate the debate on the relative chronology that is usually suggested. The identification of materials reveals the circulation of goods and trade. The richness of pictorial effects and techniques demonstrates a knowhow long considered as typical of the late Gothic period, including the use of oil in the binding media. Most of the information collected in the Belgian corpus matches the results of analyses carried out on sculptures from other European regions, both in terms of the evolution of their appearance and of their techniques. These observations make it possible to put forward the hypothesis of a fast and oral transmission not only within local workshops but in the broader European global context.